If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.6(x + -5) = -10 + 4 Reorder the terms: 0.6(-5 + x) = -10 + 4 (-5 * 0.6 + x * 0.6) = -10 + 4 (-3 + 0.6x) = -10 + 4 Combine like terms: -10 + 4 = -6 -3 + 0.6x = -6 Solving -3 + 0.6x = -6 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 0.6x = -6 + 3 Combine like terms: -3 + 3 = 0 0 + 0.6x = -6 + 3 0.6x = -6 + 3 Combine like terms: -6 + 3 = -3 0.6x = -3 Divide each side by '0.6'. x = -5 Simplifying x = -5
| (16+2x)(28+2x)=748 | | 4x-4-2x=4 | | p-46=-11 | | 0.92+x(0.2)=y | | 8=2w+7/6+7w+6/2 | | (-5u+7w-z)/(u+w-z) | | b/7-13=12 | | Y-5x=13 | | x^2+10x=200 | | 4(4x+3)+6=16x+18 | | 120(n-3)=600 | | 4(y+3)+y=2(y+4)-4 | | 5.4x+3.4=14.2 | | 2x^2+5x^4-12x^3=0 | | 2x-3/9+x+1/2=x-4 | | -24+6x=8(3x+6) | | -b+1.8=5.3 | | 4x-5/3-7x=2/1 | | -5(t-3)+7t=4t-2 | | 10p+9+11=-2(2p+4)-3(2p-2) | | (x+3)2-4=0 | | 6n+12=78 | | -7=-7.5z-(-7z+3) | | log[4](2x-9)-log[4](x-8)=3 | | 3(x+9)=6x | | 2=x-4(2x+3) | | 8(r+2)=54 | | 7x=12x-45 | | (+15)+(-7)+(+1)= | | y=57-2 | | 2x+4x=3x+3 | | 3(x-9)=6x |